EFEKTIVITAS PENYIARAN BERITA MELALUI RADIO DI KALANGAN GENERASI Z (RENTANG USIA 16-23 TAHUN) - Sandra, Kusnul Ika (Balai Diklat Keagamaan Surabaya, 2018)
The shift in mass media consumption occurred along with theemergence of more sophisticated media. Among the media thereis one medium that has a big a big roles before other mediacome, that is radio. The research was conducted to know theeffectiveness of radio in broadcasting the main informationnews considering many other media more sophisticated andmore varied in spreading the news to the audience especiallyadolescents belonging to the category of Z generation. Thisresearch is considered as a quantitative descriptive one, whereresearcher wants to reveal the condition or reality occurstailored to the issues raised by researcher. The result is 50 % ofthe total 35 respondents of Z Generation considers that radio isstill effective used to get the news. Although this not as themain mass media, 48.6% of respondents Z Generation considersthat radio is more often used for listening to entertainment,such as music, compared to broadcast programs news. ZGeneration considers that in the present era of radio as a massmedia bearer news has begun in substitution with other massmedia such as online mass media for various reasons.